Pattern and factors associated with workplace violence towards doctors in southern part of Karnataka: a cross-sectional study - K., Vinay Kumar; M. R., Ravi; N., Naveen; Saligrama Rajaiah, Vijayashree; M. N., Damayanthi; S. K., Sukanya (International Journal Of Community Medicine And Public Health, 2024)
Background: Workplace Violence (WPV) is a globally growing health problem among Doctors, Doctors are at continuous risk of facing aggression at the workplace. This study aimed to evaluate the magnitude and factors associated with violence against doctors. Methods: An online survey of doctors working in a tertiary care hospital in Southern Karnataka was done by using the modified version of the workplace violence (WPV) in the health sector questionnaire, developed by the World Health Organization. Results: Out of the 96 participants, 69 doctors (71.9%) reported being exposed to violence at their workplace in the past 6 months. 92.3% of post graduate, 96% of the residents from other states have experienced WPVs. The most common type of WPV was verbal abuse (70%), and the perpetrators were relatives of the patients (85.5%). The possible perceived reasons for WPV were security issues (34%), workplace environment (28.9%). Conclusions: The present study suggests that more than half of the doctors working in a tertiary care hospital in Southern Karnataka face WPV. Reporting of the incidents and taking strict actions against the violence is lacking and it must be strengthened to reduce prevalence of WPVs.